PENERAPAN MODEL PEMBELAJARAN AKTIF TIPE INDEX CARD MATCH UNTUK MENINGKATKAN PRESTASI BELAJAR SISWA PADA MATERI SISTEM GERAK - Nafisah Hanim (Universitas Islam Negeri Ar-Raniry, 2017)
The research aims to determine improvement of student achievement through the application of active learning model type Card Match at SMPN 1 Indrapuri Aceh Besar. The method used is quasi experiment with experimental design used is One Group pretest-posttest design. The sample in this study were students of class VII4 which amounted to 24 students, sample determination was done by random sampling. Data collection was done by written test in the form of multiple choice questions which amounted to 25 questions. Data analysis using t test formula at significant level 0,05. The results showed that the average pretest value is 39.03 while the average posttest value is 77.11 with the N-gain value of 38.07. Analysis of t test at significant level Î± = 0.05 with degrees of freedom 23 of the distribution table obtained tcount value higher than the ttable value of 23.64> 1.71. The conclusion of this research is the application of active learning model of Index Card Match type can improve student achievement of SMPN 1 Indrapuri Aceh Besar on the concept of motion system.